Kondisi Stres Akademik Siswa SMA Negeri di Kota Padang - Taufik Taufik; Ifdil Ifdil; Zadrian Ardi (Jurnal Konseling dan Pendidikan, 2013)
This research conduct base from increasing the National Examination standards from recent years, and overload student’s learning activity in Senior High School (SMA). These conditions as triggers stress students, from a long time, its influence on their learning. Based that, the research is to identify level of student academic stress, and differences base gender, and school location. This research use Cluster Random Sampling. Samples are grouped into 3 (three), that’s school is located in downtown, midtown and the Suburbs. Research findings show that there are 15% of student’s stress academic at low levels of, 71,8% experiencing stress academic at medium level, and 13.2% of students experiencing stress academic at high level. There was no significant difference between the academic stress Student SMAN in Padang by location and gender. These research findings can then be an important basic need for guidance and counseling services in order to decrease the level of stress of academic students in Padang city, so that they can learn by making every effort that is optimal.